Identifying and appraising outcome measures for severe asthma: a systematic review. Issue 4 (3rd April 2023) - Rattu, Anna; Khaleva, Ekaterina; Brightling, Chris; Dahlén, Sven-Erik; Bossios, Apostolos; Fleming, Louise; Chung, Kian Fan; Melén, Erik; Djukanovic, Ratko; Chaudhuri, Rekha; Exley, Andrew; Koppelman, Gerard H.; et al.
Background: Valid outcome measures are imperative to evaluate treatment response, yet the suitability of existing end-points for severe asthma is unclear. This review aimed to identify outcome measures for severe asthma and appraise the quality of their measurement properties. Methods: A literature search was performed to identify "candidate" outcome measures published between 2018 and 2020. A modified Delphi exercise was conducted to select "key" outcome measures within healthcare professional, patient, pharmaceutical and regulatory stakeholder groups. Initial validation studies for "key" measures were rated against modified quality criteria from COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN). The evidence was discussed at multi-stakeholder meetings to ratify "priority" outcome measures. Subsequently, four bibliographic databases were searched from inception to 20 July 2020 to identify development and validation studies for these end-points. Two reviewers screened records, extracted data, assessed their methodological quality and graded the evidence according to COSMIN. Results: 96 outcome measures were identified as "candidates", 55 as "key" and 24 as "priority" for severe asthma, including clinical, healthcare utilisation, quality of life, asthma control and composite. 32 studies reported measurement properties of 17 "priority" end-points from the latter three domains. Only the Severe Asthma Questionnaire and Childhood Asthma Control Test were developed with input from severe asthma patients. The certainty of evidence was "low" to "very low" for most "priority" end-points across all measurement properties and none fulfilled all quality standards. Conclusions: Only two outcome measures had robust developmental data for severe asthma. This review informed development of core outcome measures sets for severe asthma. This study identified and appraised the validity of selected outcome measures for severe asthma with input from key stakeholders. Only the Severe Asthma Questionnaire and Childhood Asthma Control Test had robust developmental data for severe asthma. https://bit.ly/3F7Xwcn